2018
DOI: 10.1123/jsr.2015-0080
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Composition on Functional Movement Screen™ Scores in College Football Players

Abstract: Increased BF% and BMI relate to lower composite FMS™ and individual FMS™ test scores, indicating potentially poor movement patterns in larger National Collegiate Athletic Association football athletes. Future research should focus on examining lower extremity-specific FMS™ tasks individually from composite FMS™ scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
12
2
Order By: Relevance
“…Previous studies have reported considerably larger inverse associations between BMI and FMS scores then in the current study (r ranged from -0.3 to -0.81) [19,20,34,40,41]. Notably, several studies have reported that the strength of the association between BMI and motor coordination declines as children start to reach puberty [62,63], which might explain some of the above-mentioned disparity in findings between the current and previous research.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have reported considerably larger inverse associations between BMI and FMS scores then in the current study (r ranged from -0.3 to -0.81) [19,20,34,40,41]. Notably, several studies have reported that the strength of the association between BMI and motor coordination declines as children start to reach puberty [62,63], which might explain some of the above-mentioned disparity in findings between the current and previous research.…”
Section: Discussioncontrasting
confidence: 81%
“…Therefore, investigating relations between adiposity and FM is important for the musculoskeletal health of the mid-adolescents as well. Only a handful of studies have focused on studying movement quality and obesity in the paediatric population with the majority reporting an inverse relationship between FM and weight status [19,20,34,40,41], while only one study revealed no correlation between these two variables [42]. However, these studies have been performed on a small number of conveniently selected children, or recruited only participants with overweight/obesity, and did not include mid-adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing and monitoring body composition (BC) is an important topic in sports because of its influence on health status and physical performance [1][2][3]. In fact, an elevated fat mass percentage (FM%) negatively influences the quality of functional movement patterns, reducing physical performance in athletes [4][5][6]. Conversely, wider muscle mass areas, particularly of the upper limb, maximizes power expression and the capacity to perform repeated sprints with changes in direction [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis and monitoring of body composition is fundamental in sport, because of its relevance to athletes' health and performance, and to team success. Nicolaidis et al [1] provided solid evidence that high fat mass (FM) negatively affect the ability to exert force during jumping, whereas, Chalmers et al [2] highlighted that fat-free mass (FFM) is associated to strength and muscle power, while its increase is one of the main aims included in the injury prevention programs.…”
Section: Introductionmentioning
confidence: 99%